Perspective Imam Madzhab on Bughat Elements - Harissalam Harissalam (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2020)
The research objective in this article is to discuss the elements of the bughat radius according to Imam Ahmad bin Hanbal. The results showed that the elements of Jarimah Bughat were three actions which could show the act as an act of Jarimah Bughat. The three elements are acts of rebellion and not obeying the provisions of the Caliph, acts of rebellion carried out by prioritizing power, and having the goal of taking legitimate power.